Drag of superfluid current in bilayer Bose systems - Fil, D.V.; Shevchenko, S.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
An effect of nondissipative drag of a superfluid flow in a system of two Bose gases confined in two parallel quasi-two-dimensional traps is studied. Using an approach based on introduction of density and phase operators, we compute the drag current at zero and finite temperatures for arbitrary ratio of particle densities in the adjacent layers. We demonstrate that in a system of two ring-shaped traps the «drag force» influences the drag trap in the same way as an external magnetic flux influences a superconducting ring. This allows one to use the drag effect to control persistent current states in superfluids and opens up the possibility of implementing a Bose analog of the superconducting Josephson flux qubit.